THE MAIN COMPONENTS OF INNOVATION MANAGEMENT (The New Uzbekistan Journal of Medicine, 2025)
This research explores the critical role of innovation management in the context of higher education institutions. Drawing on key concepts such as organizational structure, leadership, and a culture of risk-taking, the study emphasizes the importance of implementing innovative management principles to enhance teaching, research, and overall institutional effectiveness. The text highlights the need for universities to embrace new approaches, technologies, and methodologies to stay competitive and address the evolving needs of students and society. By fostering a dynamic and innovative environment, universities can empower their faculty and staff to contribute to meaningful advancements in education and research.